A Review of Calendula officinalisMagic in Science - KARTHIKEYA PATIL (Journal of Clinical and Diagnostic Research, 2022)
Calendula officinalis (Calendula), a member of the Asteraceae family, is often known as English Marigold or Pot Marigold. Marigold is a fragrant herb that has been used in traditional medicine for centuries. Calendula species have been highlighted in order to better understand their diverse biological activities and modes of action. Carotenoids, flavonoids, glycosides, steroids and sterols, quinines, volatile oil, and amino acids are all found in abundance in this plant. Calendula oil is still used as an antitumour agent in medicine, which is also a wound healing agent. Among herbal medicines, Calendula suspension or tincture is used to treat acne locally, reduce inflammation, control bleeding and soothe irritated tissues. This Calendula plant’s extract, a pure chemical extracted from it, have been shown to have a variety of pharmacological properties including anti-inflammatory, antioedematous, antioxidant activity, antibacterial and antifungal activity, anti-Human Immunodeficiency Virus (HIV) and antiviral activity, wound healing and immunostimulant activity. Anticytotoxic, hepatoprotective, spasmolytic properties and also impacts on exhibiting increased levels of proinflammatory cytokines Interleukin (IL)-1 beta, IL-6, Tumor Necrosis Factor (TNF)-alpha and Interferons (IFN)-gamma and acute phase protein, C-reactive protein. C.officinalis may have an important future impact on the development of new cancer treatment strategies, and until now it has been specifically used to reduce the side-effects of radiotherapy. This review looked at the organoleptic, in-vitro, and in-vivo pharmacological activities, as well as the description, cultivation, and active chemical constituents of Calendula officinalis in order to fill in the gaps in current knowledge about this plant and to highlight its potential applications as a medicinal agent.